Variance based sensitivity analysis of 1D and 2D hydraulic models: An experimental urban flood case. (November 2018) - Chen, S.; Garambois, P.-A.; Finaud-Guyot, P.; Dellinger, G.; Mosé, R.; Terfous, A.; Ghenaim, A.
Abstract: This paper explores spatial sensitivities of 1D and 2D shallow water (SW) models of branched urban flood flows, based on an experimental data-set and a variance decomposition method for various combination of uncertainty sources. General sensitivity patterns of SW model for subcritical flows show that: simulated water height variance is explained upstream by inflow discharge and roughness whereas downstream it is fully explained by downstream water height, influence of lateral inflows propagates in both directions. High sensitivities to roughness can be local in space thus identifying the strongest hydraulic controls for orienting calibration efforts is needed. 2D sensitivities show: the filtering effect of branched network topography on inflow, the zone of influence of boundary conditions, the role of large streets as global flow pattern separators, the difference in roughness sensitivity patterns with 1D. This sensitivity analysis of SW models could be a base for studying flow path and uncertainty propagation. Highlights: GSA framework for branched urban flood flows modelling. Sobol spatial sensitivities of 1D and 2D shallow water models. Identification of hydraulic controls for various uncertainty combinations. Filtering effect of branched network topography quantified.